2018
DOI: 10.14216/kjco.18023
|View full text |Cite
|
Sign up to set email alerts
|

Use of positron emission tomography-computed tomography to predict axillary metastasis in patients with triple-negative breast cancer

Abstract: Breast cancer is the most common type of invasive cancer among women and is the second leading cause of cancer-related death. The diagnosis of breast cancer is based on clinical examination combined with imaging and is confirmed by histopathological assessment. Imaging includes bilateral mammography and ultrasonography of the breast and regional lymph nodes (LNs). Axillary lymph node (ALN) metastasis is an important prognostic factor, and the diagnosis of ALN metastasis is essential for treatment planning, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…To date, studies on the prediction of axillary metastasis using the subtypes, but not in the triple negative subtype [11]. In contrast, one study reported that PET was the optimal tool in detecting ALN metastasis in the triple negative subtype compared to the other three subtypes, with a sensitivity of 87.0% and specificity of 67.3% [12]. However, in this study, the ratio of the ALN to the primary tumor SUVmax was used.…”
Section: Discussionmentioning
confidence: 92%
“…To date, studies on the prediction of axillary metastasis using the subtypes, but not in the triple negative subtype [11]. In contrast, one study reported that PET was the optimal tool in detecting ALN metastasis in the triple negative subtype compared to the other three subtypes, with a sensitivity of 87.0% and specificity of 67.3% [12]. However, in this study, the ratio of the ALN to the primary tumor SUVmax was used.…”
Section: Discussionmentioning
confidence: 92%
“…Cha et al 17 found that SUVmax of axillary nodes was higher in the Her2-positive group than either of the luminal groups, and Youm et al 18 showed higher values in TNBC than other subtypes. This correlation was not achieved (p = 0.061) in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…And another study showed that tumor SUVmax could predict lymph node metastasis only in luminal A and HER2 positive type but not in luminal B and triple-negative type [15]. In contrast, the other study reported that PET-CT was a useful imaging tool in predicting lymph node metastasis in the triple-negative subtype compared to the other three subtypes, with a sensitivity of 87% and specificity of 67% [16].…”
Section: Discussionmentioning
confidence: 99%